Cubic CuO catalyst, and preparation method thereof - SHI GUOJUN; BAO YAN; CHEN BINBIN (2016)
The invention relates to a cubic CuO catalyst, and a preparation method thereof. The cubic CuO catalyst is obtained via loading gamma-type Al2O3 with CuO, wherein loading amount of CuO is controlled to be 0.5 to 4mmol/g, and the phase of CuO is cubic phase. According to the preparation method, chemical vapor deposition is adopted to prepare the gamma-Al2O3 loaded cubic CuO catalyst, and the cubic CuO catalyst is used for preparing benzenediol and p-benzoquinone via phenol oxidation. The pure loaded-type cubic CuO catalyst is obtained at a sublimation temperature ranging from 160 to 190 DEG C, at a substrate temperature ranging from 260 to 300 DEG C, under a vacuum degree ranging from 0.07 to 0.09MPa, in 2 to 5h. The obtained cubic CuO catalyst possesses excellent low temperature activity and selectivity in reaction used for preparing benzenediol and p-benzoquinone via phenol hydroxylation.